Helicobacter pylori in Costa Rica, more than a decade of research - Montero-Campos, Virginia (2019)
Research conducted at the Biotechnology Research Center (CIB) in water for human consumption from Costa Rica, a total of 112 drinking water samples from 20 cantons located in areas of low and high incidence of gastric cancer in the country were analyzed; successful culture and molecular identification of Helicobacter pylori with the glmM marker in 39% of the samples from high incidence areas and in 7.5% of the samples from low incidence areas was achieved. In addition, drinking water samples (n = 44) of Costa Rican aqueducts with chlorination treatment in selected areas with high prevalence of gastric cancer were also analyzed, as well as samples of water for human consumption from Panama (n = 44) of aqueducts that supply water not treated for human consumption in the province of Chiriquí. In the case of samples from Costa Rica, it was determined that 79.5% of the samples were positive for H. pylori; eliminating atypical values, the quantification of the bacteria was determined in 3.6 × 103 copies/100 mL of water. It was determined for Panama that 86% of the samples were positive for the presence of H. pylori with a value of 3.3 × 102 copies/100 mL water. The difference in values between the aqueducts in both countries revealed an environmental distribution of the bacteria of epidemiological interest in each case that can explain the difference between gastric cancer rates between both countries.